SOCIAL ENTREPRENEURSHIP ORIENTATION EFFECT ON FIRM PERFORMANCES: A CONCEPTUAL FRAMEWORK - Hasrul Hashom; Ahmad Shabudin Ariffin; Rohafiz Sabar; Hartini Ahmad (Food, Agriculture and Natural Resources - NETWORKS, 2020)
Research on social entrepreneurship was variously published and has been dedicated to conceptual frameworks, synthesizing and integrating past study in fast growing economies environment. conducted to examine its performances in many angles. This is important since social entrepreneurship has become as new trend in business model globally and the trend also absorb in Malaysia`s commercial market. Although numerous studies have been done, specifically research on social entrepreneurship orientation not yet been tested over firm performance especially company with social mission objective. Therefore, this concept paper will focus and check on direct relationship on social entrepreneurship orientation as independent variable toward firm`s performance. Furthermore, this paper focuses on reviewing the social entrepreneurship performances especially in Malaysia. This study is important since the social entrepreneurship continue to grow blossomly for future country economy development as per stated by join partnership report by British Council, Yayasan Hasanah, United Nation ESCAP and Ministry of Entrepreneurship Development in “The State Of Social Enterprise In Malaysia”. To have an impact of the result, this study will implement Theory of Structural Contingency since it was widely used in previous research especially to test the ‘fit’ factors between variables. This conceptual paper able to develop understanding on diversity, meaning, and evolution of the social entrepreneurship phenomenon in the context of emerging economies; including to facilitate the community of social entrepreneurship researchers and practitioners respectively. It also can advance research in this domain with the aid of the proposed framework and the research questions proposed for future research.